Oral Health Equals Total Health: A Brief Review - Yap, Adrian U. (Journal of Dentistry Indonesia, 2017)
Erythema multiforme (EM) is an acute mucocutaneous hypersensitivity reaction characterized by skin eruptions with or without oral or other mucous membrane lesions. The main two variants are erythema minor and erythema major. Oral disease with typical EM lesions has been suggested as a third variant of EM. Known as oral EM, it is reported less and has no target lesions unlike the other two types, in its primary presentation. Objective: To report a manifestation of a rare case of oral EM and discuss various forms of EM including its management. Case report: A 22-year-old male patient reported with a complaint of oral and lip ulcers and severe pain for the past 7 days. The patient reported spontaneous onset of the lesions in the form of vesicles after consuming unknown artificially colored food items. The vesicles ruptured within two days leaving ulcers on the lips and the intraoral mucosa, with blood encrustations. The patient was unable to take food, was admitted for hydration, and was kept on corticosteroids. It took around three weeks for the patient to completely recover. Conclusion: The positive his¬tory of artificially colored food intake followed by the sudden onset of lesions and eruptions on the lips and oral mucosa led us to the diagnosis of oral EM. Early recognition and timely intervention benefits patients because the lesions associated with EM and related disorders can compromise life.